Heat hypersensitivity is attenuated with altered expression level of spinal astrocytes after sciatic nerve injury in TRPV1 knockout mice. (September 2021) - Baba, Kazuhiko; Kawasaki, Makoto; Nishimura, Haruki; Suzuki, Hitoshi; Matsuura, Takanori; Fujitani, Teruaki; Tsukamoto, Manabu; Tokuda, Kotaro; Yamanaka, Yoshiaki; Ohnishi, Hideo; Yoshimura, Mitsuhiro; Maruyama, Takashi; et al.
Highlights: Heat sensitivity was attenuated in TRPV1 knockout mice after partial sciatic nerve ligation. Astrogliosis was impaired in TRPV1 knockout mice after partial sciatic nerve injury. Chemical inhibition of astrocytes induced heat hyposensitivity. TRPV1 was co-localized in astrocytic GFAP positive cells in the spinal dorsal horn. TRPV1 may modulate heat sensitivity via spinal astrogliosis. Abstract: Transient receptor potential vanilloid 1 (TRPV1) modulates pain. Studies have indicated that TRPV1 is upregulated in the spinal dorsal horn in the neuropathic pain model, but its mechanism is unknown. Here, we examined the mechanism by which TRPV1 modulates neuropathic pain by employing partial sciatic nerve ligation (pSNL) in adult male C57BL/6 J (wild-type: WT) and TRPV1 knockout ( Trpv1-/- ) mice. We analyzed mechanical/heat sensitivities (von Frey test/hot plate test) and glial/neuronal activities (Iba-1/GFAP/FosB by immunofluorescence) in laminae I and II in the L5 ipsilateral dorsal horn of the spinal cord. Mechanical/heat sensitivities, expression levels of microglial Iba-1 and astrocytic GFAP, and the number of FosB-positive neurons were significantly increased on days 7 and 14 in the pSNL group compared with the sham-operated and non-operated groups of both WT and Trpv1-/- mice. While mechanical sensitivity was comparable between WT and Trpv1-/- mice, the threshold against heat sensitivity was markedly prolonged in Trpv1-/- than WT mice on day 14 after pSNL. Conversely, the increment of FosB positive neurons was significantly attenuated in Trpv1-/- than WT mice on days 7 and 14 after pSNL. These results suggest that TRPV1 may modulate thermal perception via increased astrocytes in the dorsal horn of the spinal cord.